Estimation of leachate volume and treatment cost avoidance through waste segregation programme in Malaysia - Rangga, Josfirin Uding; Syed Ismail, Sharifah Norkhadijah; Rasdi, Irniza; Karuppiah, Karmegam (Universiti Putra Malaysia Press, 2024)
This study aims to calculate the avoided leachate volume and treatment cost from waste segregation practices compared to the existing waste disposal methods of landfilling. The mathematical equations were used to analyse the waste segregation rate, leachate volume and treatment cost. The study findings reveal that 99.4 of mixed waste was disposed of in landfills, resulting in an annual generation of 565 thousand cubic meters (m3) of leachate with an estimated treatment cost of MYR 19.82 million (USD 4.36 million). The segregated waste, which accounts for only 0.06, reduces 354 m3 in leachate volume and a cost-saving of MYR 12.42 thousand (USD 2.73 thousand) in the treatment expenses per year. The findings concluded that waste segregation practice could reduce waste management costs by reducing leachate production and treatment costs and environmental impacts.